FASHION SEBAGAI PENCIPTAAN IDENTITAS DIRI REMAJA DI KOTA DENPASAR - Pane, Dessy Monica; Punia, I Nengah; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
This research attempted to analyze the self-identity constructed by fashion, but this identity is a camouflage because relying on the certain symbols that is artificial, in which it is able to trap the society in experiencing the unnecessary consumptive lifestyle. This study applied descriptive explanative type of qualitative approach with the analysis of the consumer society theory by Jean P. Baudrillard. The result showed that adolescents in post-modern era tend to use fashion as a means in creating an adhesive identity to themselves. Recently, adolescents try to attract more attention from their surroundings and can be seen distinctly from their own characteristics. Therefore, adolescents have particular meaning of fashion, which one of them is fashion as a means of self-expression and the growth of self-confidence on the actor. In addition, fashion also gives the impact for the actor, both social and economic impact. From social impact they will perceive as more famous person and will be considered in their social interaction and has a connection for their field of hobbies and work with the people who have the same interests. On the other hand, some adolescents perceive the negative social impact, such as being insulted from other people who are less agree with the different appearance with the uncommon fashion. Hereafter, the economic impact that is perceived by adolescents is being improvident to buy famous branded items with irrational prices to give a perfect support for their appearance. However, most adolescents outsmart this by shopping in the thrift shop (flea market), where they can obtain branded items with low prices, in order to avoid to be improvident. Hence, some of the adolescents in Denpasar are smart consumer, because they are not fully co-opted by the logic of late capitalism, namely, the logic of improvident fashion. Keywords: Fashion, Self-identity, Consumer Society